Tradisi A’matoang Pasca Pernikahan di Kecamatan Binamu Kabupaten Jeneponto; Analisis Hukum Islam - Muh Arya Pratama; Arif Rahman (Universitas Islam Negeri Alauddin Makassar, 2021)
The main problem in this research is related to the post-msrriage tradition of a’matoang which is still maintained today. This type of research is field research (field research) which is raised from the observation of social facts which is studied using a normative or syar'i theological approach and a sociological approach. The research data sources were obtained from the community and local community leaders. The method used in this research is direct observation and information gathering through interviews and is supported by reference studies related to the tradition of a'matoang after marriage in Binamu District, Jeneponto Regency. Data processing techniques performed in the from of data reduction filtering important information related to the object of research, presenting research data and drawing conclusions. The results of this study indicate that the people in Binamu District, Jeneponto Regency still maintain the tradition of a'matoang after marriage. However, based on the viewpoint of Islamic law, the a’matoang tradition dies not have an element of associating partners with Allah because its purpose is only as a a symbol to maintain and strengthen kinship ties that are solely due to Allah, so that wiil be an act that is also blessed by Allah SWT. The implications of this research include: 1) For the people of Binamu District, Jeneponto Regency who still maintain the ancestral and sacred values of a'matoang so that they are maintained but in a reasonable context and do not deviate from Islamic teachings and if this culture results in more harm. great for the doer, then let it be abandoned; 2) The a’matoang tradition that is carried out after this marriage is expected not only as a form of showing off or being proud of others but with a sacred purpose, namely to glorify and respect the groom's family and to hope for the pleasure of Allah to have a sakinah mawadah household warahmah